Postoperative back pain following epidural anesthesia: Can dexamethasone help? - Saghafinia, Masoud; Nafissi, Nahid; Motamedi, Mohammad Hosein Kalantar; Asadollahi, Reza (Asian Journal of Pharmaceutics (AJP), 2014)
Epidural anesthesia (EA) is a central neuraxial block with many applications. Improvements in equipment, drugs and techniques have made it a popular and versatile anesthetic procedure. However, back pain is a common postoperative complaint. We aimed to determine the effect of dexamethasone added to EA to reduce post-epidural anesthesia backache. Fifty-nine patients scheduled undergoing surgery were randomly assigned to two groups: Case group (30 patients) received 300 mg lidocaine (1.5%) plus 1/200,000 epinephrine and 4 mg dexamethasone (1CC) for epidural anesthesia, and a control group (29 patients) received 300 mg lidocaine (1.5%) with 1/200000 epinephrine and 1CC normal saline (placebo). Patients were visited 12, 24 and 48 hours after operation, and the severity of post-epidural backache was recorded according to a visual analogue scale pain score. In the case group, 29 patients (96.6%) had mild back pain, and only 1 patient (3.3%) had moderate back pain and none experienced severe back pain post-operatively. In the control group, 19 patients (65.5%) had mild backache, 9 patients experienced moderate and 1 had severe backache. Mean backache severity score of the case group was statistically lower than the control group (P = 0.003), after 12 h (P = 0.001), 24 h (P = 0.00) and 48 h (P = 0.002) postoperatively. Dexamethasone addition may be effective in reducing severe to moderate post-epidural anesthesia backache in EA patients. Key words: Dexamethasone, epidural anesthesia, post-epidural backache